2018
DOI: 10.15405/epsbs.2018.07.02.11
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Reporting: A Comparison Between Malaysian And Singapore Public Listed Companies

Abstract: An effective disclosure of corporate information has increasingly becoming more critical as the world market begins a long shift toward a higher share of market-based financing. In the future, IR is expected to play a bigger role in promoting understanding of interdependencies between various capitals that a company has and support integrated thinking, decision-making and actions that focus on the creation of value over the short, medium and long term. Motivated by the gap among prior IR related studies partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…Companies got an average score between 75% and 100% for subcategories. This result is in line with Abdullah et al (2018), which found that the risks and opportunities element is the most disclosed element for Malaysian and Singapore companies achieving scores 83% and 84%. The analysis notices several risks disclosed in the IR (e.g., financial, operational, regulatory, market and technology).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Companies got an average score between 75% and 100% for subcategories. This result is in line with Abdullah et al (2018), which found that the risks and opportunities element is the most disclosed element for Malaysian and Singapore companies achieving scores 83% and 84%. The analysis notices several risks disclosed in the IR (e.g., financial, operational, regulatory, market and technology).…”
Section: Resultssupporting
confidence: 90%
“…This result is in line with Abdullah et al (2018), which found that the risks and opportunities element is the most disclosed element for Malaysian and Singapore companies achieving scores 83% and 84%.…”
Section: Risks and Opportunitiessupporting
confidence: 86%
See 1 more Smart Citation
“…Second, the Malaysian regulatory bodies have paid more attention to the disclosure of IR, as the Malaysian Code on Corporate Governance (MCCG) 2017 recommended that large companies should adopt IR practice in their annual reports (Securities Commission Malaysia [SCM], 2017). However, IR practice is still in its infancy stage in Malaysia (Abdullah et al , 2017). Although a few Malaysian studies have addressed IR disclosure (Ghani et al , 2018; Jamal and Ghani, 2016; Singh et al , 2012; Wen and Heong, 2017; Masduki and Zaid, 2019; Abdullah et al , 2017; Amirrudin et al , 2020), they all used data from the period before the revised MCCG 2017 was adopted and implemented, when IR was rarely practiced in the Malaysian market.…”
Section: Introductionmentioning
confidence: 99%
“…However, IR practice is still in its infancy stage in Malaysia (Abdullah et al , 2017). Although a few Malaysian studies have addressed IR disclosure (Ghani et al , 2018; Jamal and Ghani, 2016; Singh et al , 2012; Wen and Heong, 2017; Masduki and Zaid, 2019; Abdullah et al , 2017; Amirrudin et al , 2020), they all used data from the period before the revised MCCG 2017 was adopted and implemented, when IR was rarely practiced in the Malaysian market. In addition, ambiguous and different IR measurements are used by these studies.…”
Section: Introductionmentioning
confidence: 99%